Pemanfaatan Bahan Organik dalam Perbaikan Beberapa Sifat Tanah Pasir Pantai Selatan Kulon Progo - Hasibuan, Andi Surya Zannah (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
An experiment about the utilization of organic matter to improve some properties of sandy soils of south beach of Kulon Progo was conducted in Green House, Faculty of Agriculture, Universitas Muhammadiyah Yogyakarta. The research was carried out in experimental method which arranged in Completely Randomized Design (CRD) with 5 treatments. The treatments were P0 = without compost application (Control), P1 = 30 ton per hectare of cow dung compost, P2 = 30 ton per of Â hectare of poultry compost, P3 = 30 ton per hectare of Angsana leaves compost, P4 = 30 ton per hectare of gamal leaves compost, each treatment were replicated 5 times. The result showed that utilization of organic matter could improve the properties of sandy soils of south beach of Kulon Progo. Angsana leaves were the best organic matter sources in improving the physical and chemical of soil properties, such as water content, bulk density, soil porosity, and soil C-Organic content.